2022
DOI: 10.1111/jdv.18218
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world evidence from the non‐interventional, prospective, German multicentre PERSIST study of patients with psoriasis after 1 year of treatment with guselkumab

Abstract: Background PERSIST was a prospective, non-interventional, long-term, German multicentre study of patients with moderate-to-severe psoriasis receiving guselkumab, an approved monoclonal antibody that binds to the p19 subunit of interleukin (IL)-23, in a real-world setting.Objectives Evaluation of the efficacy and safety of guselkumab, and its effect on health-related quality of life (HRQoL), in patients with moderate-to-severe psoriasis who have received 52 weeks of treatment.Methods Patients (≥18 years old) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…7 In a prospective, non-interventional and multi-center German PERSIST study analyzing 303 psoriasis patients undergoing guselkumab treatment, the overall drug survival at week 52 was 92.4%. 9 While guselkumab trended towards increased drug survival relative to ixekizumab and secukinumab, there were no significant differences in these three drug survival rates. However, other studies have alternatively reported that secukinumab and guselkumab exhibit higher rates of drug survival (90% vs 88%) relative to ixekizumab (82%).…”
Section: Discussionmentioning
confidence: 90%
“…7 In a prospective, non-interventional and multi-center German PERSIST study analyzing 303 psoriasis patients undergoing guselkumab treatment, the overall drug survival at week 52 was 92.4%. 9 While guselkumab trended towards increased drug survival relative to ixekizumab and secukinumab, there were no significant differences in these three drug survival rates. However, other studies have alternatively reported that secukinumab and guselkumab exhibit higher rates of drug survival (90% vs 88%) relative to ixekizumab (82%).…”
Section: Discussionmentioning
confidence: 90%
“…The PASI 75 and PASI 90 response rates reported for the other IL-23p19 inhibitors, guselkumab and risankizumab, in real-life settings appear consistent with those observed in this study with TIL. [37][38][39][40][41][42] Likewise, recent real world evidence studies reporting PASI response rates for all three IL-23p19 inhibitors from the same cohort have found very similar effectiveness. 35,43 In addition to the DLQI questionnaire, the Skindex-16 measure was utilized in the TRIBUTE study to comprehensively assess the impact on HRQoL.…”
Section: System Organ Class Term Preferred Termmentioning
confidence: 97%
“…Summary drug survival curves in blue, separate studies in grey. A Secukinumab [ 24 26 , 33 , 34 , 39 41 , 44 , 46 , 48 , 50 , 51 , 53 , 62 , 64 , 68 , 70 , 72 , 74 , 80 85 ], B ixekizumab [ 23 , 32 , 33 , 39 , 40 , 42 44 , 46 , 49 , 62 , 70 , 81 , 84 , 85 ], C brodalumab [ 39 , 40 , 58 , 62 , 84 87 ], D guselkumab [ 29 , 30 , 33 , 35 , 37 , 43 , 44 , 50 , 59 , 70 , 84 , 85 , 88 , 89 ], E risankizumab [ 27 , 50 , 84 , 85 , 90 ], ...…”
Section: Resultsmentioning
confidence: 99%